COVID-19 and Sickle Cell Disease–Related Deaths Reported in the United States. (March 2022) - Payne, Amanda B.; Schieve, Laura A.; Abe, Karon; Hulihan, Mary; Hooper, W. Craig; Hsu, Lewis L.
Sickle cell disease (SCD) is associated with increased risk of poor health outcomes from respiratory infections, including COVID-19 illness. We used US death data to investigate changes in SCD-related mortality before and during the COVID-19 pandemic. We estimated annual age- and quarter-adjusted SCD-related mortality rates for 2014-2020. We estimated the number of excess deaths in 2020 compared with 2019 using the standardized mortality ratio (SMR). We found 1023 SCD-related deaths reported in the United States during 2020, of which 86 (8.4%) were associated with COVID-19. SCD-related deaths, both associated and not associated with COVID-19, occurred most frequently among adults aged 25-59 years. The SCD-related mortality rate changed <5% year to year from 2014 to 2019 but increased 12% in 2020; the sharpest increase was among adults aged ≥60 years. The SMR comparing 2020 with 2019 was 1.12 (95% CI, 1.06-1.19). Overall, 113 (95% CI, 54-166) excess SCD-related deaths occurred in 2020.